2016
DOI: 10.1111/grow.12170
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Interactive Effects of Brokerage Roles on Innovation in Clustered Firms

Abstract: Social network analysis has generated a great number of research findings in organizational and management literatures. Moreover, the so-called territorial clusters have been represented through the network metaphor. However, while scholars primarily examine the network structure and the internal heterogeneity, we have particularly analyzed the diverse types or roles of informational brokers which firms can develop. Furthermore, we posit that innovation generated by these firms is moderated by their own capabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 101 publications
(175 reference statements)
1
22
1
2
Order By: Relevance
“…The Gould and Fernandez's (1989) brokerage typology has been used in range of scholarly applications, including examining brokerage in innovation (Belso-Martínez et al, 2017), education (Watling Neal et al, 2019), policy and knowledge (Jasny and Lubell, 2015), social media (Abul-Fottouh, 2018), organizational studies (Diani, 2003;Boari and Riboldazzi, 2014;Kirkels and Duysters, 2010), and cross-border organisational networks (Walther and Reitel, 2013). There is yet limited application in economic geography (see however Boari et al, 2017;Vicente et al, 2011), with brokerage of firm networks between places loosely described as 'bridging', 'brokering' or 'mediating' functions (e.g. Liu et al, 2014;.…”
Section: Insert Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The Gould and Fernandez's (1989) brokerage typology has been used in range of scholarly applications, including examining brokerage in innovation (Belso-Martínez et al, 2017), education (Watling Neal et al, 2019), policy and knowledge (Jasny and Lubell, 2015), social media (Abul-Fottouh, 2018), organizational studies (Diani, 2003;Boari and Riboldazzi, 2014;Kirkels and Duysters, 2010), and cross-border organisational networks (Walther and Reitel, 2013). There is yet limited application in economic geography (see however Boari et al, 2017;Vicente et al, 2011), with brokerage of firm networks between places loosely described as 'bridging', 'brokering' or 'mediating' functions (e.g. Liu et al, 2014;.…”
Section: Insert Figurementioning
confidence: 99%
“…Short et al, 1996). Thus, despite extensive theorization of what brokerage entails for individual and/or other actor networks (Boari et al, 2017;Diani, 2003;Gould and Fernandez, 1989;Kadushin, 2002;Kirkels and Duysters, 2010;Walther and Reitel, 2013), there remains a knowledge gap when applied to territorial units such as cities, small states, and other areal configurations (for an exception,…”
Section: Introductionmentioning
confidence: 99%
“…Ruef () and Amara and Landry () concluded that the ability of the entrepreneurs to obtain non‐redundant information from social networks is essential for innovation. More recently, Boari, Molina‐Morales, and Martínez‐Cháfer () showed that brokerage relationships based on interactions between firms are positive to foster innovation. Finally, at the regional level, Hauser et al () found that associations are the social capital dimension most strongly related to patenting activity in European regions.…”
Section: Social Capital Associational Activity and Innovationmentioning
confidence: 99%
“…As instituições de suporte (IDS) compreendem as organizações orientadas para atuar em um determinado território, que provêm serviços especializados (Brusco, 1993), agem como repositórios de conhecimento e facilitam o desenvolvimento da competitividade às firmas locais (Molina-Morales & Martínez-Fernández, 2010). As IDS se traduzem em universidades, centros de pesquisa e/ou organizações governamentais, associações empresariais e fontes financiadoras públicas ou privadas (Boari, Molina-Morales & Martínez-Cháfer, 2017), que possuem a habilidade de obter informação fora do aglomerado territorial -e/ou da rede -e internalizá-la junto às empresas (Molina-Morales & Martínez-Fernández, 2010).…”
Section: Instituições De Suporteunclassified